2022
DOI: 10.1152/ajpcell.00404.2021
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phosphate transport by NAD+/NADH in brush border membrane vesicles

Abstract: Nicotinamide is an important regulator of Pi homeostasis after conversion into NAD+/NADH. In this work, we have studied the classical inhibition of Pi transport by these compounds in the brush border membrane vesicles (BBMV) of rat kidney and rat intestine, and we examined the effects in Opossum Kidney (OK) cells and in phosphate transporter-expressing Xenopus laevis oocytes. In BBMV, NAD+ required preincubation at either room temperature or on ice to inhibit Pi uptake in BBMV. However, no effects were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Therefore, the administration of NRCl and its derivatives triggers altered expression of key BBM genes involved in digestion, and absorption, with additional effects on intestinal microbiota composition and function. Further and as was previously suggested, these functional changes, as demonstrated via gene expression of key BBM proteins (zinc transporter, inflammatory cytokines, absorptive proteins, and mucin), were previously associated with BBM tissue physiological and morphometric alterations, as increased villi size [ 24 , 50 , 93 , 94 , 95 , 96 , 97 ]. These alterations may potentially also be associated with increased proliferation of cellular populations that hold essential roles in BBM function, including, enterocytes, and therefore, increased villus surface area (the intestinal digestive and absorptive surface), and goblet cells (produce and secrete mucus), both number and diameter in intestinal villi and crypt [ 18 , 22 , 24 , 47 , 50 , 93 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, the administration of NRCl and its derivatives triggers altered expression of key BBM genes involved in digestion, and absorption, with additional effects on intestinal microbiota composition and function. Further and as was previously suggested, these functional changes, as demonstrated via gene expression of key BBM proteins (zinc transporter, inflammatory cytokines, absorptive proteins, and mucin), were previously associated with BBM tissue physiological and morphometric alterations, as increased villi size [ 24 , 50 , 93 , 94 , 95 , 96 , 97 ]. These alterations may potentially also be associated with increased proliferation of cellular populations that hold essential roles in BBM function, including, enterocytes, and therefore, increased villus surface area (the intestinal digestive and absorptive surface), and goblet cells (produce and secrete mucus), both number and diameter in intestinal villi and crypt [ 18 , 22 , 24 , 47 , 50 , 93 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 56%
“…These inhibitors both target sodium–phosphate transporters such as those of the SLC34 family; however, they have distinct putative modes of action. It is suggested that PFA has a competitive effect directly blocking the uptake site, whereas NAD + acts non-competitively by indirectly effecting transporter function through transporter modification ( Loghman-Adham, 1996 ; Sorribas et al, 2019 ; Lucea et al, 2022 ). While evidence exists for sodium-dependent phosphate transporters in daphnids (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additional recently published findings include the demonstration that FGF23 decreases apical membrane NPT2A expression by stimulating endocytosis of NPT2A into an endolysosomal pathway [23], a mechanism that had been suspected but not explicitly demonstrated. Lucea et al [24] appear to have settled a longstanding debate about the inhibitory effects of NADþ on phosphate transport, demonstrating that only after degradation was NADþ able to inhibit phosphate transport in a cell culture model, and identifying the increase in local phosphate release and the breakdown product ADP-ribose as the responsible agents [24]. Finally, a recent manuscript showed that inhibition of the prorenin receptor blocked the inhibitory effect of high phosphate on renal phosphate transport through inhibition of FGF23 release [25].…”
Section: Andandmentioning
confidence: 99%